DINAMIKA KELOMPOK TANI DI DESA NETPALA KECAMATAN MOLLO UTARA KABUPATEN TIMOR TENGAH SELATAN - Jeningsi Frans; Ignatius Sinu; Selfius P. N. Nainiti (Buletin Ilmiah Impas, 2020)
This study aims to find out : (1) the dynamics of farmer groups in Netpala Village, North Mollo District, South Central Timor District, (2) the constraints faced by farmer group members in applying the dynamics of farmer group elements in Netpala Village, North Mollo Subdistrict South Central Timor District. The research method used is a survey method. The location of the sample was determined by purposive sampling in the village of Netpala. The research population is all farmers who are members of farmer groups in Netpala Village, and the sample of farmer was taken proportionate random sampling from 110 farmers from five farmer groups, therefor obtained 52 farmers. The analysis used in this study was a qualitative descriptive analysis and a Likert scale. The results showed the majority of respondents in productive age were 46 (88.46%) of formal education was low 22 (44.23%), non-formal education was classified as high where there were 44 (84.61%). The average dynamics level of the eight elements of farmer group dynamics in the Netpala village is dynamic (69%), the dynamics level of group goals is quite dynamic (62%), group structure is dynamic (88%), the structure of task functions is dynamic (100%) %), the structure of group development and group development is dynamic (67%), the compact group structure is dynamic (85%), the structure of the group atmosphere has the same score (50%), the pressure structure of the group is quite dynamic (44%), the structure group effectiveness is classified as dynamic (100%). Constraints faced with the eight elements of group dynamics, group goals (61%), group structure (11%), coaching and group development (30%), group cohesiveness (15%), group atmosphere (50%), group pressure (55%), group effectiveness (0%) or no feedback.